Lo spazio sociale europeo Atti del convegno internazionale di studi Fiesole (Firenze), 10-11 ottobre 2003 - Leonardi, Laura (Atti, 2005)
For the last few years a group of European historians, under the direction of Professor Robert Frank of the Sorbonne University of Paris, has been conducting an extensive research aimed at identifying the characteristics of an European "space" in the context of the integration process. As part of the group's activities the conference, whose the proceedings are collected here, was held in October 2003 in Florence. The meeting had as its objective a reflection on the emergence and development of a "European social space" beginning from the origins of the integration process, in which historians, sociologists, political scientists and some lead actors of this important community dynamic had the opportunity to meet.